Enhancing Concrete Properties With Rubber Additives: Experimental Analysis And Performance Evaluation - Saif, Yaqoob (Indonesian Journal Publisher, 2025)
This research investigates the effect of adding recycled rubber to concrete mixes as part of efforts to enhance environmental sustainability and improve the mechanical properties of concrete. The study focuses on evaluating the mechanical and physical performance of rubberized concrete by analyzing its properties such as compressive strength, tensile strength, and workability. Partial replacement of rubber by 0% to 15% of fine aggregate in concrete was studied, with standard tests conducted to determine the effect of rubber on overall performance. The importance of the research lies in providing a dual solution of reducing environmental waste from used tires, while improving some properties of concrete in non-structural applications. The results show that rubberized concrete achieves important advantages such as improved flexibility, abrasion resistance, and light weight, despite a slight decrease in compressive strength. The research also highlights the potential of using rubberized concrete in non-structural applications such as pavements, road barriers, and shock absorption systems. The research concludes by recommending further studies to improve the adhesion between rubber and concrete mix components, while exploring innovative applications to expand the use of rubberized concrete in sustainable construction projects.